Activation and allosteric modulation of a muscarinic acetylcholine receptor - Kruse, Andrew C.; Ring, Aaron M.; Manglik, Aashish; Hu, Jianxin; Hu, Kelly; Eitel, Katrin; Hübner, Harald; Pardon, Els; Valant, Celine; Sexton, Patrick M.; Christopoulos, Arthur; Felder, Christian C.; et al. (Nature, 2013)
Despite recent advances in crystallography and the availability of G-protein-coupled receptor (GPCR) structures, little is known about the mechanism of their activation process, as only the β 2 adrenergic receptor (β 2 AR) and rhodopsin have been crystallized in fully active conformations. Here we report the structure of an agonist-bound, active state of the human M2 muscarinic acetylcholine receptor stabilized by a G-protein mimetic camelid antibody fragment isolated by conformational selection using yeast surface display. In addition to the expected changes in the intracellular surface, the structure reveals larger conformational changes in the extracellular region and orthosteric binding site than observed in the active states of the β 2 AR and rhodopsin. We also report the structure of the M2 receptor simultaneously bound to the orthosteric agonist iperoxo and the positive allosteric modulator LY2119620. This structure reveals that LY2119620 recognizes a largely pre-formed binding site in the extracellular vestibule of the iperoxo-bound receptor, inducing a slight contraction of this outer binding pocket. These structures offer important insights into the activation mechanism and allosteric modulation of muscarinic receptors. © 2013 Macmillan Publishers Limited. All rights reserved.